An Arduino microcontroller based RLC meter - Hoque, Mohammad Mominul; Motakabber, S. M. A.; Ibrahimy, Muhammad Ibn; Alam, A. H. M. Zahirul; Akter, Mahfuza (IEEE, 2019)
An RLC meter is a single electronic instrument or device which is capable to measure the Resistance (R), Inductance (L) and Capacitance (C). This instrument has wide applications in electrical and electronics laboratory, industry and engineering research works. Nowadays, a large variety of RLC meter is available. The high precision RLC meter is slow responding, bulky size, higher operational power and expensive. However, many applications do not need very high accuracy measurement, for this reason, this paper has proposed a simple and moderate precision RLC meter based on Arduino microcontroller which would overcome the existing issues. The proposed design has been verified by simulation and experimentally. The results show good compliance with theory and experiment; in addition, it shows moderate accuracy.